Nobility and domestic conviviality in the paintings of archduchess Maria Christine - Michael Yonan (Theatrum Historiae)
Scholars have long identified Jean-Jacques Rousseau's writings as central texts to the history of the family. Eighteenth-century transformations to the family concept affected all families, including those of high social status; despite being monarchs, royal families could not shield themselves from larger social changes affecting family definitions in general. This paper addresses that phenomenon by examining a social activity in which imagined identities could be explored and represented, namely art, through a discussion of the Habsburg Archduchess Maria Christine of Austria (1742-1798). Daughter of Empress Maria Theresa, Maria Christine founded with her husband Albert of Sachsen-Teschen the collection that forms the basis of the modern Graphische Sammlung Albertina in Vienna and was herself an accomplished amateur painter. By inserting her monarchical family into scenes representing bourgeois activities, Maria Christine utilized painting to explore aspects of her monarchical life that otherwise could not be represented in official art.